Relationship of anaemia and morbidities among children aged 5-14 years in a resettlement area, Delhi - Kasdekar, Pankaj Motilal; Prasuna, Josyula; Sulania, Anika; Rasania, Sanjeev Kumar; Dwivedi, Nidhi (Indian Journal of Community Health, 2015)
Partnership for Child Development (1998), “The anthropometric status of school children in five countries in the Partnership for Child Development”. Proceedings of the Nutrition Society 57: 149- 158. World Health Organization. Anaemia. WHO (2010). World Health Organization (WHO). WHO global database on anaemia: Worldwide prevalence of anaemia 1993-2005. Ge¬neva: WHO, 2008a. [Cited 2014 Aug 24]. Available from: URL: http://www.who. int/vmnis/anaemia/prevalence/en/index. html World Health Organization (WHO). Health in Asia and the Pacific: Reproductive health, child and adolescent health, nutrition, and health for older persons. Geneva: WHO, 2008b. [Cited 2014 Jul 6]. Available from: URL: http://www.wpro.who.int/publica-tions/Health+in+Asia+and+the+Pacific. Html. National Family Health Survey (NFHS-3) (2005-06), Nutrition in India, Ministry of Health and Family Welfare Government of India, World Health Organisation. Criteria Anaemia 1985; WHO.World Bank. Rema N, Vasanthamani G. Prevalence of nutritional and lifestyle disorders among school going children in urban and rural areas of Coimbatore, Tamilnadu: Indian Journal of Science and Technology 2011; Vol. 4 (2). Bhoite R, et al. Magnitude of malnutrition and Iron deficiency anaemia among rural school children: Asian J Exp Biol Sci 2003; Vol 2(2): 354-361. Handa R, Ahamad F, Prasad R, “Assessment of nutritional status of 7-10 Years School going children of Allahabad District”. Middle-East Journal of Scientific Research 2008; 3(3):109-115. Verma A, et al. Factors influencing anaemia among girls of school going age (6-18 years) from the slums of Ahmedabad city. IJCM 2004; Vol 29 (1). Hasan I, Zulkifle M, A study of malnutrition in government school children in the field area of azad nagar Bangalore, India. (MD thesis).2010.Dept. of preventive and social medicine; National Institute of Unani Medicine. Ananthakrishnan S, Pani SP, Nalini P. A comprehensive study of morbidity in school age children. Indian Pediatr. 2001 Sep;38(9):1009-17. PubMed PMID: 11568376.[PubMed] Chakma T, Rao PV, Tiwary RS. Prevalence of anaemia and worm infestation in tribal areas of Madhya Pradesh. J Indian Med Assoc. 2000 Sep;98(9):567, 570-1. PubMed PMID: 11291791.[PubMed] Dambhare DG, Bharambhe MS et al. Nutritional Status and Morbidity among School going Adolescents in Wardha, a Peri-Urban area. Online Journal of Health and Allied Sciences Volume 9, Issue 2; Apr-Jun 2010 Shakya SR, Bhandary S, Pokharel PK. Nutritional status and morbidity pattern among governmental primary school children in the Eastern Nepal. Kathmandu Univ Med J (KUMJ). 2004 Oct-Dec;2(4):307-14. PubMed PMID: 16388242.[<a href="file:///D:/Dropbox/IJCH/Vol%2027,%20No%202%20(2015)/6.%20Master%20File/Shakya%20SR,%20Bhandary%20S,%20Pokharel%20PK.%20Nutritional%20status%20and%20morbidity%20pattern%20among%20governmental%20primary%20school%20children%20in%20the%20Eastern%20Nepal.%20Kathmandu%20Univ%20Med%20J%20(KUMJ).%202004%20Oct-Dec;2(4):307-14.%20PubMed%20PMID:%2016388242.">PubMed]